Absorption, distribution and excretion of acronycine in rats - LIU Chang-xiao; JI Xiu-juan (Acta Pharmacologica Sinica, 2016)
The metabolism of acronycine was studied in normal rats. Acronycine was extracted from various biological materials with chloroform and determined at 280 nm. The pharmacokinetic parameters were assessed by the two-compartment open model: t ka =0.32, t α=0.97 and t β=38 h, Kα=2.128, ke =0.081, k12=0.495, k21=0.161h-1, Cmax=25.55 μg/ml, TPK=0.83h, and AUC=292 Μg/ml.h. The drug concentrations in the liver 27.5, spleen 20.0, heart 19.0, lung 18.0, kidney 14.0, muscle 10.0, brain 3.0μg/g and in the blood 12.0μg/ml. In 72 h, 58.7%of the administered dose was found in urine and only 4.5% in feces.